(Social Exchange at the Graduation Celebration of Students after the Thesis Examination of the Postgraduate Social Sciences Students of UNP) - rammayani, winda; Erianjoni, Erianjoni (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the phenomenon of social exchange that occurs in the celebration of student graduation after the Thesis exam in the Social Sciences Department. The main focus of this study is on the tradition of giving gifts as a symbol of appreciation, solidarity, and strengthening social relations among students. The research method used is a qualitative approach with a case study type, involving interviews, observations, and documentation studies. The results of the study indicate that giving gifts, such as flower bouquets, sling bags, and snacks, not only function as a sign of appreciation, but also create a cycle of reciprocity in students' social relations. Economic factors and social background influence the variation in the form of gifts, with students who have better financial capabilities tending to give more luxurious gifts. This study also reveals the importance of emotional support, both through congratulations and motivational words, as an integral part of the graduation celebration. Overall, this tradition of giving gifts strengthens solidarity and builds togetherness among students, despite challenges related to economic disparities that can affect individual experiences in the celebration. This study is expected to provide deeper insight into the social dynamics in student graduation celebrations and their contribution to the formation of closer social relations.